El cerebro humano y su relación con el proceso de aprendizaje - Yucra Camposano, Jennifer (2016)
The present article focuses on the relationship among the brain and the learning process, approaching in cognitive and socio-affective processes involved in this process. In addition, some recommendations from neurodidactic are mentionedto work in the classroom to consolidate learning.